G3 Hedonic olfaction in huntington's disease. (13th September 2016) - Marxreiter, Franz; Mrochen, Anne; Kozay, Christina; Regensburger, Martin; Klucken, Jochen; Winkler, Jürgen; Kohl, Zacharias
Abstract : Background: Huntington's disease (HD) features a broad range of neuropsychiatric symptoms. In particular depression, apathy, and anhedonia are frequently present in HD. Anhedonia and apathy are observed as core symptoms of depression in HD but also as distinct features of HD independent from major depression. Therefore, methods helping to dissociate these symptoms are an important need for a precise diagnostic workup. Assessing anhedonia by focusing on hedonic perception of a sensory stimulus may be particularly helpful in HD. Aims: In this study, we examine anhedonia by measuring the perception of pleasantness of odours in HD patients compared to controls. Methods: By using the "Sniffin'Sticks®" odour identification test we assess hyposmia. In order to dissociate hedonia and olfaction we use additional olfactory sticks with 22 odours assessing intensity and pleasantness of odours. Pleasantness of odours is measured on a visual 9-point scale. For the assessment of hedonia and apathy the Snaith-Hamilton-Pleasure-Scale (SHAPS) and the Starkstein scale are applied respectively. Depression is measured using the Zung Self-Rating Depression Scale and the Beck Depression Inventory II. Perspective: The hypothesis of this study is that the assessment of hedonic olfaction in HD allows discriminating anhedonia and apathy from depression. To test our hypothesis we will compare the hedonic perception of odours between HD patients and age and gender matched controls. Furthermore, we will correlate hedonic olfaction with the questionnaire-based assessment of depression, apathy and anhedonia. These data will be compared to our previously published findings that have shown reduced hedonic olfaction in Parkinson's disease.